MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN TEKNIK MNEMONIC PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP NEGERI 11 LUBUKLINGGAU - Yanti, Leni; Arikarani, Yesi; Helandri, Joni (Universitas Muhammadiyah Tapanuli Selatan, 2024)
One of the factors for the low learning outcomes of PAI is the lack of interest of students in learning PAI. Therefore this research was conducted because of the learning outcomes of class VII students of PAI. 1 SMP Negeri 11 Lubuklinggau is still low due to the lack of technical development in the learning process. In this study aims to improve student learning outcomes in accordance with the Maximum Completeness Criteria (KKM). Which in this study used the Classroom Action Research (CAR) method which was carried out in 2 cycles with data collection techniques using observation, documentation, interviews, and tests. From the research that has been carried out, the results of this study are that there is an average percentage of learning outcomes of students with the Mnemonic Technique in the learning process with the following details: 1) in the application of this Mnemonic Technique there is an increase in the learning outcomes of students in each cycle, this can be proven for learning outcomes in cycle I reached 72.81% (good), while in cycle II it reached a percentage of 86.25% (very good), 2) there was an increase in student learning outcomes in each cycle. It was proven that the average score of students in cycle I was 21.06 with a percentage of 40.69%, while in cycle II it had increased by 13.44 with a percentage of learning outcomes of 18.45%, so that in cycle II it was declared successful because it had achieve performance indicators.